(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Several shells of megalodontids have been extracted from densely packed coquinas coming from the Upper Triassic of northern Calabria (Southern Italy). Such a mode of preservation, which is unusual for these bivalves, has made it possible to detect the morphological characters regarding both the shell and inner mould. Morphological variability has been identified by means of biometrical analysis, which allows them to be separated into two morpho-groups both belonging to the genus Triadomegalodon. Here they are considered to be the extreme morphotypes of a single species, which has some peculiar characteristics with respect to the known species. However, the bad state of the preservation of the shells, which are affected by disarticulation, abrasion and fragmentation, induces us to act with caution establishing a new taxon [Triadomegalodon sp. n. aff. tofanae (Hörnes)]. Some aspects of functional morphology led us to consider Triadomegalodon as a semi-infaunal bivalve, unable to burrow actively.